Phytochemical Investigation and Cytotoxic Effect against A459 Cell Line via Iraqi Portulacaria afra (f. Protulacaea) Ethyl Acetate Whole Plant Extract - Nabaa M. Ibrahem (Iraqi Journal of Pharmaceutical Sciences, 2025)
Despite decades of advanced medical study, extracts from coniferous plants have recently been found to be effective against tumor disorders. One of the most prevalent cancers in the world is lung cancer in which every two and a half minutes, lung cancer is discovered in the world. Portulacaria afra Jacq. (spekboom or pork bush) is a medicinal plant belonging to the family of Didieraceae, that contains (7) genera and (20) species .The plant's historical advantages and mythical significance include the usage as a diuretic, for sores, for persistent rash, for heartburn, and for rheumatism. Additionally, it has been claimed that P. afra exhibits antibacterial, antifungal, antioxidant anti-inflammatory and cancer-preventing properties.  However, data on chemical content in the ethylacetate extract is still limited, the main objective of this study is to detect the presence of different polyphenolic constituents in the plant extract by reverse phase-high performance liquid chromatography and evaluate the cytotoxic effect of ethyl acetate extract of this plant on human lung cancer (A549) cell line using the 3-[4,5- dimethylthiazole-2-yl]-2,5-diphenyltetrazolium bromide (MTT) assay. Phytochemical analysis of the Portulacaria afra ethyl acetate extract led to identify five polyphenolic constituents designated as phenolic acids (caffeic, sinapic, and ferulic acid), and flavonoids (qeurcetine and myrcetine). According to estimates, the ethyl acetate extract that contain the high concentration of polyphenolic constituents gave the best findings as cytotoxic against lung cancer A549cell line with IC50 value of 0.47 µg/ml.